If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -14 = 62 Reorder the terms: -14 + 2x = 62 Solving -14 + 2x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2x = 62 + 14 Combine like terms: -14 + 14 = 0 0 + 2x = 62 + 14 2x = 62 + 14 Combine like terms: 62 + 14 = 76 2x = 76 Divide each side by '2'. x = 38 Simplifying x = 38
| 7-^3/2 | | fy+3=gx+-15 | | 10x^3+6x^2=0 | | -9x-40= | | 3x-2/3(2x-1)=4 | | 6+3n= | | 36x^4-81x^7=0 | | -6x-4(7x+13)=186 | | 20/6x-7/6=9/6 | | 0.18=x^12 | | 4=15r-7 | | 6(x-3)=-2(x-7) | | 6x+18=10x-6 | | 47=5x-(7-4x) | | 7x+3y=50000 | | -(3x+5)=2x | | -d+4e=-3 | | -6(x-6)=3(0+x) | | 0.5=0.4 | | R+2-3=4 | | x+(x-20)=78 | | 11x-7(-4+2x)=-14 | | 7x+3=56 | | -4x^2-5.5x+5=0 | | -5x-4(-3x+15)=3 | | -6(-v-3y+4)= | | 2x^2-4x+4=25 | | 0.8x-4=1.5x+0.2 | | 48.15/45 | | 0.8x-4=1.5+0.2 | | f(x)=x^4+8x^2-12 | | x^2-2x=10.5 |